High burden of polypharmacy and comorbidity in persons with psoriatic arthritis: an analysis of claims data, stratified by age and sex. Issue 1 (9th March 2023) - Albrecht, Katinka; Regierer, Anne Constanze; Strangfeld, Anja; Marschall, Ursula; Callhoff, Johanna
Abstract : Objective: To assess polypharmacy in women and men with psoriatic arthritis (PsA). Methods: From the German BARMER health insurance database, 11 984 persons with PsA and disease-modifying antirheumatic drug therapy in 2021 were included and compared with sex-matched and age-matched controls without inflammatory arthritis. Medications were analysed by Anatomical Therapeutic Chemical (ATC) groups. Polypharmacy (≥5 concomitant drugs) was compared by sex, age and comorbidity using the Rheumatic Disease Comorbidity Index (RDCI) and the Elixhauser Score. The mean difference in the number of medications between persons with PsA and controls was estimated using a linear regression model. Results: Compared with controls, all ATC drug classes were significantly more frequent in persons with PsA, most commonly musculoskeletal (81% vs 30%), immunomodulatory (56% vs 2.6%), cardiovascular (62% vs 48%), alimentary tract/metabolic (57% vs 31%) and nervous system (50% vs 31%) drugs. Polypharmacy was significantly higher in PsA (49%) compared with controls (17%), more frequent in women (52%) compared with men (45%) and strongly increased with age and comorbidity. For each unit increase of the RDCI, the age-adjusted number of medications increased by 0.98 (95% CI 0.95 to 1.01) units in men and 0.93 (95% CI 0.90 to 0.96) units in women. Compared with controls, the number of medications in PsA (mean 4.9 (SD 2.8)) was 2.4 (95%CI 2.34; 2.43) units higher in women and 2.3 (95% CI 2.21 to 2.35) units higher in men. Conclusions: Polypharmacy is common in PsA and is composed of PsA-specific medication as well as frequent medications for comorbidities, equally affecting women and men.